As contribuições do programa Trainee para o processo de aprendizagem organizacional: um estudo de caso na Companhia de Água e Esgoto do Ceará - Braide, Jamile Maia (2007)
This present work has as goal the investigation of the way the trainee program contributed to the constitution of a learning environment in the organization based on the organizational learning model by DiBella and Nevis (1999), which is divided in two parts, facilities and learning orientations, having three phases: acquisition, dissemination and use of knowledge in the organization, permeating also other theories and concepts of organizational learning, knowledge management, trainee programs and coaching process. The research was explorative and descriptive, by a bibliographical survey, as well as a case study, using as instrument for the information gathering the application of two models of a half-structured interview and two questionnaire models on three research groups. The first group compound of Directors and Human Resources Manager, the second group compound of members of the Executive Committee and the Management and Evaluation Commission of the Trainee Program and the third group of Trainees. The information was treated quantitatively and qualitatively. The research allowed identifying the facility, however one part in a higher intensity than the other, distinguishing in the joint vision of the three groups the imperative inquiry, the organizational curiosity, the continued education and the multiple defenders. Regarding the learning orientations predominated in all three groups: the internal knowledge, the knowledge reserve in an explicit way, the incremental learning and the development of the individual as much as the collective abilities.